2021
DOI: 10.3390/en14217113
|View full text |Cite
|
Sign up to set email alerts
|

Coopetitive Platform: Common Benefits in Electricity and Gas Distribution

Abstract: Simultaneous collaboration and competition, or coopetition, has so far been studied among firms or non-profit organizations, leaving the public arena largely unexplored. This study focuses on identifying and measuring common benefit generation by local government actors in coopetition. We purposefully choose a metropolis composed of 41 municipalities setting to identify and measure those effects of coopetition that cannot be achieved by individual actors alone. We use real data and tariffs to run simulations t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Tak więc w przypadku ekonomii zrównoważonego rozwoju głównym obszarem gospodarowania jest wielowymiarowy makrosystem obejmujący jednocześnie społeczeństwo i gospodarkę oraz środowisko. Jest to holistyczne spojrzenie na przedmiot ekonomii zrównoważonego rozwoju (Czakon i in., 2021). Każde społeczeństwo boryka się z wykluczeniem społecznym, wahaniem i nierównomiernym rozłożeniem dobrobytu oraz niedostatecznym staraniem o ochronę klimatu.…”
Section: Pojęcie I Istota Zrównoważonego Rozwojuunclassified
“…Tak więc w przypadku ekonomii zrównoważonego rozwoju głównym obszarem gospodarowania jest wielowymiarowy makrosystem obejmujący jednocześnie społeczeństwo i gospodarkę oraz środowisko. Jest to holistyczne spojrzenie na przedmiot ekonomii zrównoważonego rozwoju (Czakon i in., 2021). Każde społeczeństwo boryka się z wykluczeniem społecznym, wahaniem i nierównomiernym rozłożeniem dobrobytu oraz niedostatecznym staraniem o ochronę klimatu.…”
Section: Pojęcie I Istota Zrównoważonego Rozwojuunclassified
“…Only the determination of the benefits allows for you to start the connection [39]. The value resulting from this procedure is defined as a significant increase in profitability and as an increase in the value of the combined enterprise [40].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of the conducted research have shown that to ensure energy security by resigning from coal mining, disproportionate investment outlays and high costs need to be incurred to secure the transformation of the energy sector in Poland. However, this requires a good condition of the Polish economy and high GDP to meet the financial requirements of such a transformation [73][74][75][76][77].…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%